Pengaruh Penggunaan Sabut Kelapa Terhadap Pengolahan Limbah Cair Rumah Makan - Al Adawiyah; Indah Anggraini; Fadhil Raid; Ferdian saputra; Ratna Yeni; Virda Septianingsih (Prosiding Seminar Nasional Biologi, 2022)
Oil and fat content in restaurant wastewater is an element that can cause body pollution and hinder further processes in the Wastewater Treatment Plant. For this reason, efforts need to be made to eliminate its content in wastewater, namely by doing filtration. The purpose of this study was to analyze the effectiveness of coco fiber as a filter for waste oil (fat) in restaurant wastewater. The research started from the process of making coco fiber and filtration containers until it was continued to the filtration treatment process. The results of the study showed that there was a significant difference between before and before the service using coconut fiber with 1 time, 2 times, and 3 times music. With the result that the waste is not filtered the color of the water is cloudy blackish brown, available, lots of food residue and smells, and the fish die in the 25th minute. for 1 time the water is cloudy brown, slightly smelly, the fish move slowly, and die in the 40th minute. to offer 2 times the water is cloudy, slightly, the fish move actively to the surface, and die in the 70th minute. for 3 times fishing for active fish, swimming at the bottom of the container, cloudy water no desire. Coconut coir fiber is effective as a filtration medium for treating restaurant wastewater containing oil (fat). It is recommended to do further research by adding filtration.